Fungal Bioremediation of Selenium-Contaminated Industrial and Municipal Wastewaters - Sabuda, Mary C.; Rosenfeld, Carla E.; DeJournett, Todd D.; Schroeder, Katie; Wuolo-Journey, Karl; Santelli, Cara M. (Frontiers in Microbiology, 2020)
Selenium (Se) is an essential element for most organisms yet can cause severe negative biological consequences at elevated levels. The oxidized forms of Se, selenate (Se(VI)) and selenite (Se(IV)), are more mobile, toxic, and bioavailable than the reduced forms of Se such as volatile or solid phases. Thus, selenate and selenite pose a greater threat to ecosystems and human health. As current Se remediation technologies have varying efficiencies and costs, novel strategies to remove elevated Se levels from environments impacted by anthropogenic activities are desirable. Some common soil fungi quickly remove Se (IV and VI) from solution by aerobic reduction to solid or volatile forms. Here, we perform bench-scale culture experiments of two Se-reducing Ascomycota to determine their Se removal capacity in growth media conditions containing either Se(IV) or Se(VI) as well as in Se-containing municipal (~25 µg/L Se) and industrial (~2000 µg/L Se) wastewaters. Dissolved Se was measured throughout the experiments to assess Se concentration and removal rates. Additionally, solid-associated Se was quantified at the end of each experiment to determine the amount of Se removed to solid phases (e.g., Se(0) nanoparticles, biomass-adsorbed Se, or internal organic selenoproteins). Results show that under optimal conditions, fungi more efficiently remove Se(IV) from solution compared to Se(VI). Additionally, both fungi remove a higher percentage of Se from the filtered municipal wastewater compared to the industrial wastewater, though cultures in industrial wastewater retained a greater amount of solid-associated Se. Additional wastewater experiments were conducted with supplemental carbohydrate- or glycerin-based carbon products and additional nitrogen- and phosphorous-containing nutrients in some cases to enhance fungal growth. Relative to unamended wastewater experiments, supplemental carbohydrates promote Se removal from municipal wastewater but minimally impact industrial wastewater removal. This demonstrates that carbon availability and source impacts fungal Se reduction and removal from solution. Calculations to assess the leaching potential of solid-associated Se from fungal biomass show that wastewater Se release will not exceed regulatory limits. This study highlights the considerable potential for the mycoremediation of Se-contaminated wastewaters.